2016
DOI: 10.15294/biosaintifika.v8i3.6957
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Polysaccharide Krestin from Coriolus versicolor Extract on Phagocytic Activity and Capacity of Mus musculus Exposed by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is an opportunistic bacterium that causes infections in human. The wall cell of its bacteria contains lipopolysaccharide as virulency factors to protect it from human immunity. Lipopolysaccharide can inhibit phagocytosis in the body. Polysaccharide krestin (PSK) from Coriolus versicolor extract contains β-glucan that can increase phagocytic activity and capacity. This research aimed to identify the effect on polysaccharide krestin from C. versicolor extract on phagocytic activity and cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Novak and Vetvicka (2008) research showed that βglucan increased both proliferation of macrophage and cytokine in bone marrow, thus more phagocytes were recruited to the infected organs. Wahyuningsih et al (2016) stated that polysaccharide krestin from C. versicolor increased both phagocytic activity and capacity on Mus musculus exposed to Pseudomonas aeruginosa.…”
Section: Effect Of Crude Polysaccharides Of C Versicolor On Phagocytmentioning
confidence: 99%
“…Novak and Vetvicka (2008) research showed that βglucan increased both proliferation of macrophage and cytokine in bone marrow, thus more phagocytes were recruited to the infected organs. Wahyuningsih et al (2016) stated that polysaccharide krestin from C. versicolor increased both phagocytic activity and capacity on Mus musculus exposed to Pseudomonas aeruginosa.…”
Section: Effect Of Crude Polysaccharides Of C Versicolor On Phagocytmentioning
confidence: 99%
“…From all infection cases in Indonesia, 7.1% was identified as nosocomial cases (World Health Organization, 2011) In recent years, using immunomodulator to enhance the immune response has proven to be an effective way to increase resistance to disease . Study conducted by Wahyuningsih et al (2016) showed a significant increase of phagocytic activity in treatment group treated by polysaccharides from Coriolus versicolor. Polysaccharides from plants have been known as an important immunostimulatory agent with broad spectrum, low toxicity and few side effects (Cho et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Wahyuningsih et al . [12] reported that PS of C. coriolus could enhance the response of immunoglobulin against Pseudomonas aeruginosa . Another study was also reported that polysaccharide from C. versicolor induce B-cell activation and enhance cytokine production [13].…”
Section: Introductionmentioning
confidence: 99%